METHODS FOR DEVELOPING THE APPROACH STEP TECHNIQUE IN VOLLEYBALL ATTACK. (International journal of artificial intelligence, 2025)
This article examines the technical aspects of the volleyball attacker’s approach steps and effective methods for their improvement. The research focuses on athletes of beginner and intermediate levels, applying a combined program of plyometric, coordination, and technical exercises. The measured indicators include approach speed, vertical jump height, attack accuracy, and hitting efficiency. The study aims to determine how specialized and progressive training improves approach rhythm and overall attacking performance. The scientific novelty lies in integrating perceptual and cognitive load training with traditional mechanical exercises, enabling athletes to develop game-like decision-making and movement coordination under realistic match conditions.